2005
DOI: 10.1007/s10570-004-3885-6
|View full text |Cite
|
Sign up to set email alerts
|

New Method for Determining the Degree of Cellulose I Crystallinity by Means of FT Raman Spectroscopy

Abstract: A Raman crystallinity index -Xc Raman -characterizing the degree of crystallinity of partially crystalline cellulose I samples was created, utilizing the crystallinity dependence of CH 2 bending modes. For calibration, physical mixtures containing different mass fractions of crystalline cellulose I and its amorphous form were prepared. Crystallinities from 0 to 60% were generated. Relative intensity ratios of the Raman lines I 1481 cm À1 and I 1462 cm À1 characterizing crystalline and amorphous parts of cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
109
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 172 publications
(115 citation statements)
references
References 18 publications
4
109
1
1
Order By: Relevance
“…Crystallinity measurements using Raman on semicrystalline polymers including cellulose (Stuart 1995;Paradkar et al 2003;Schenzel et al 2005) have been performed. The principle behind Raman methodology is the same as in FT-IR and NMR and has to do with using the spectral features whose intensity, bandwidth, and/or position are affected by crystallinity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crystallinity measurements using Raman on semicrystalline polymers including cellulose (Stuart 1995;Paradkar et al 2003;Schenzel et al 2005) have been performed. The principle behind Raman methodology is the same as in FT-IR and NMR and has to do with using the spectral features whose intensity, bandwidth, and/or position are affected by crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…The principle behind Raman methodology is the same as in FT-IR and NMR and has to do with using the spectral features whose intensity, bandwidth, and/or position are affected by crystallinity. To develop FT-Raman-based cellulose I crystallinity quantitation method, Schenzel et al (2005) used the weak bands at 1,462 and 1,481 cm -1 (CH 2 bending modes) in conjunction with spectral deconvolution. However, considering that the intensities of the selected bands are quite low and that the process of deconvolution is not free of the band fitting problems (Maddams 1980;Meier 2005), a better approach is desired.…”
Section: Introductionmentioning
confidence: 99%
“…Even at higher NaOH concentrations (18.25% or 27.5%) there was an appreciable extent of gel formation in CMC water solutions if the initial pulp had a high fraction of cellulose II. The cellulose crystallinity after the carboxymethylation reaction was quantified by analysing the FT Raman spectral data of the samples, using the models described earlier (Schenzel and Fischer 2005;Schenzel et al 2009). In this manner, the contents of crystalline and amorphous cellulose in the original dissolving pulp as well as the average content of cellulose I / cellulose II before and after its alkaline pre-treatment and in the CMC samples were determined.…”
Section: Resultsmentioning
confidence: 99%
“…The crystallinity of cellulose plays an important role in the accessibility and longevity of cellulosic fiber (Awadel-Karim et al 1999;Schenzel et al 2005). Li and Pickering (2008) and Nasir et al (2013a) studied the effect of laccase on cellulosic fiber and observed an up to 22% and 10% increase in the crystallinity index, respectively.…”
Section: Crystallinity Index Improvementmentioning
confidence: 99%